Upgrading leadership's crystal ball : five reasons why forecasting must replace predicting and how to make the strategic change in business and public policy /: five reasons why forecasting must replace predicting and how to make the strategic change in business and public policy. ([2014]) - Bauer, Jeffrey C
No abstract available